Mapping the perceived impacts of a social innovation program on women’s agency and life satisfaction - Tbaishat, Dina; Qtaishat, Lina; Eggerman, Jannik Joseph; Panter-Brick, Catherine; Dajani, Rana (Frontiers in Sociology, 2025)
IntroductionCross-cultural research measuring how women perceive their sense of agency and catalyze social innovation has been limited. We conducted a mixed-methods study to learn about women’s agency and life satisfaction, while evaluating the perceived benefits of a social innovation program (We Love Reading), in the UAE which, in 2022, launched a nationwide reading promotion strategy.Methods and resultsWe implemented the Sense of Agency (SoA) scale and Cantril Ladder of Life Scale with a sample of 78 female Emirati students, then conducted two Fuzzy Cognitive Mapping (FCM) sessions with 13 respondents. The FCM sessions helped to develop local definitions of agency and life satisfaction, map causal relationships, and run scenarios to identify program benefits. This highlighted 6 core dimensions of personal and relational agency—ability, control, strength, authority, freedom of action, and responsibility. We Love Reading boosted several aspects of agency and life satisfaction.DiscussionOur findings suggest that We Love Reading can help change mindsets and meet a fundamental policy goal related to reading habits and knowledge empowerment in the Arab World. They show the need for mapping causal reasoning in systematic ways, taking into account different dimensions of agency in environments where social innovation can flourish.